Leung Yuen-sang. The Shanghai Taotai. Linkage Man in a Changing Society, 1843-1890. Honolulú: University of Hawaii Press, 1990. 237 pp. (Asian Studies at Hawaii, núm. 39) - Connelly, Marisela (El Colegio de México, 1993)
-